Cultivation of sexually mature Brugia malayi in vitro. - Riberu, W; Atmosoedjono, S; Purnomo; Tirtokusumo, S; Bangs, M; Baird, J (1990)
Sexually mature male and female Brugia malayi were developed from third stage larvae after 60 days in the in vitro culture system described by Franke and others in 1987 (Am J Trop Med Hyg 37: 370-375). Between 75 and 100 days in culture, many worms produced living microfilariae. Each gravid female produced 200-1,500 microfilariae/day.